Teologi AhmAdiyAh dulu, SekArAng, dAn AkAn dATAng di indoneSiA - A. malik, Ridwan (Jurnal Penelitian, 2013)
THE THEOLOGY OF AHMADIYAH IN THE PAST, PRESENT, AND FUTURE IN INDONESIA. In Indonesia, the existence of Ahmadiyah got the anarchist criticism from some quarters, although there is a small group that defends it. Among the cons against Ahmadis, who put forward the reason that Ahmadiyah includes the cult because it had violated the principles of Islam. Among people supporting Ahmadiyah are more likely to look at the human side, that is “man” Ahmadiyah has a right to breathe the air of freedom in Indonesia. In historical records, Ahmadiyah has two strongholds, the stronghold of Lahore which is still on the rack of islam and the stronghold of Qadyan that is beyond the principles of Islam. In Indonesia, it is unclearly identified which one is included stronghold of Lahore and whicah one is included the Qadyan camp. Attitudes and this research should be encouraged in order to establish a more objective assessment process against the Ahmadiyah. keywords: Ahmadiyah, Lahore, Qodyan, Indonesia.Abstrak Di Indonesia, eksistensi Ahmadiyah mendapat kecaman anarkis dari sebagian kalangan, walaupun masih ada sebagian kecil golongan melakukan pembelaan. Kalangan yang kontra terhadap Ahmadiyah, yang dikedepankan adalah alasan bahwa Ahmadiyah termasuk aliran sesat karena telah melanggar prinsip ajaran Islam. Adapun kalangan yang pro terhadap Ahmadiyah lebih cenderung melihat pada sisi kemanusiaan, yaitu “manusia” Ahmadiyah berhak menghirup udara kebebasan di Indonesia. Dalam catatan sejarah, Ahmadiyah memiliki dua kubu, yaitu kubu Lahore yang masih berada dalam jalur prinsip Islam dan kubu Qadyan yang berada di luar prinsip ajaran Islam. Di Indonesia, belum jelas teridentifikasi atau terinventaris mana yang termasuk kubu Lahore dan mana yang termasuk kubu Qadyan. Sikap dan penelitian inilah yang mesti digalakkan dalam rangka menuju proses penilaian yang lebih objektif terhadap aliran Ahmadiyah.kata kunci: Ahmadiyah, Lahore, Qodyan, Indonesia.